Balloon-Assisted Percutaneous Transhepatic Antegrade Embolization with 2-Octyl Cyanoacrylate for the Treatment of Isolated Gastric Varices with Large Gastrorenal Shunts. (3rd April 2019) - Wang, Guangchuan; Meng, Dongxiao; Huang, Guangjun; Pei, Qingshan; Zhao, Lianhui; Shi, Yongjun; Zhang, Mingyan; Feng, Hua; Zhang, Junyong; Zhang, Chunqing
Abstract : Aims . To evaluate the safety and effectiveness of percutaneous transhepatic antegrade embolization (PTAE) with 2-octyl cyanoacrylate assisted with balloon occlusion of the left renal vein or gastrorenal shunts (GRSs) for the treatment of isolated gastric varices (IGVs) with large GRSs. Methods . Thirty patients with IGVs associated with large GRSs who had underwent PTAE assisted with a balloon to block the opening of the GRS in the left renal vein were retrospectively evaluated and followed up. Clinical and laboratory data were collected to evaluate the technical success of the procedure, complications, changes in the liver function using Child-Pugh scores, worsening of the esophageal varices, the rebleeding rate, and survival. Laboratory data obtained before and after PTAE were compared (paired-sample t- test). Results . PTAE was technically successful in all 30 patients. No serious complications were observed except for one nonsymptomatic pulmonary embolism. During a mean follow-up of 30 months, rebleeding was observed in 4/30 (13.3%) patients, worsening of esophageal varices was observed in 4/30 (13.3%) patients, and newly developed or aggravated ascites were observed on CT in 3/30 (10%) patients. Significant improvement was observed in Child-Pugh scores (p=0.009) and the international normalized ratio (INR) (p=0.004) at 3 months after PTAE. The cumulative survival rates at 1, 2, 3, and 5 years were 96.3%, 96.3%, 79.9%, and 79.9%, respectively. Conclusion . Balloon-assisted PTAE with 2-octyl cyanoacrylate is technically feasible, safe, and effective for the treatment of IGV associated with a large GRS.